2022
DOI: 10.1101/2022.01.17.476556
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural basis for Nirmatrelvir in vitro efficacy against SARS-CoV-2 variants

Abstract: The COVID-19 pandemic continues to be a public health threat with emerging variants of SARS-CoV-2. Nirmatrelvir (PF-07321332) is a reversible, covalent inhibitor targeting the main protease (Mpro) of SARS-CoV-2 and the active protease inhibitor in PAXLOVID (nirmatrelvir tablets and ritonavir tablets). One of the predominant SARS-CoV-2 variants emerging is the B.1.1.529 Omicron harboring a mutation at amino acid position 132 in the Mpro changing a proline to a histidine (P132H). In vitro biochemical enzymatic … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 21 publications
6
49
0
2
Order By: Relevance
“…Nirmatrelvir showed a slightly higher inhibitory potential against the P132H mutant as compared to the wild-type enzyme (wild-type: Ki = 0.933 nM, P132H: Ki = 0.635 nM). The highly similar catalytic properties of the wild-type and P132H mutants and their comparable sensitivities towards nirmatrelvir are in agreement with the fact that the P132H mutation induces no remarkable conformational changes and that the active site remains unchanged [80]. Enzyme-inhibitor interactions at the active site of P132H mutant are also identical with those of the wild-type protease (Table 1) since the P132 residue is not located in close proximity to the inhibitor-binding pocket (Figure 5a).…”
Section: Efficacy Of Nirmatrelvir Against Sars-cov-2 Variantssupporting
confidence: 80%
See 1 more Smart Citation
“…Nirmatrelvir showed a slightly higher inhibitory potential against the P132H mutant as compared to the wild-type enzyme (wild-type: Ki = 0.933 nM, P132H: Ki = 0.635 nM). The highly similar catalytic properties of the wild-type and P132H mutants and their comparable sensitivities towards nirmatrelvir are in agreement with the fact that the P132H mutation induces no remarkable conformational changes and that the active site remains unchanged [80]. Enzyme-inhibitor interactions at the active site of P132H mutant are also identical with those of the wild-type protease (Table 1) since the P132 residue is not located in close proximity to the inhibitor-binding pocket (Figure 5a).…”
Section: Efficacy Of Nirmatrelvir Against Sars-cov-2 Variantssupporting
confidence: 80%
“…In February 2022, in total, six structural coordinates of the Mpro complexed with nirmatrelvir became available in the RCSB database; the first was deposited on September of 2021 (7VH8.pdb) [ 79 ]. Other crystal structures of the same complex have also been released ( Table 1 ), and a coordinate file of only a single variant is available in the RCSB PDB database so far (7TLL.pdb); this variant contains a P132H mutation [ 80 ]. Each structure was determined using X-ray crystallography with ≤2 Å resolution.…”
Section: Proteases Inhibitors and Mutationsmentioning
confidence: 99%
“…In addition, the Pfizer team reported that PF-07321332 (nirmatrelvir) retained a potent inhibitory constant (K i ) against Omicron P132H M pro (K i = 0.635 nM), similar to WT (K i = 0.933 nM). 10 Our independent study further confirmed these results.…”
supporting
confidence: 74%
“…In addition, the Pfizer team reported PF-07321332 (nirmatrelvir) retained potent inhibition against Omicron P132H M pro (K i = 0.635 nM), similar to the potency of the WT (K i = 0.933 nM). 9 Our independent study further confirmed these results.…”
Section: Resultssupporting
confidence: 74%